2016
DOI: 10.1016/j.hrthm.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intrinsicoid deflection of the QRS complex is associated with sudden cardiac arrest

Abstract: Background Prolongation of initial ventricular depolarization on the 12-lead ECG, or delayed intrinsicoid deflection (DID), can indicate left ventricular hypertrophy (LVH). The possibility that this marker could convey distinct risk of sudden cardiac arrest (SCA) has not been evaluated. Objective To evaluate the association of DID and SCA in the community. Methods In the ongoing prospective, population-based Oregon Sudden Unexpected Death Study (Oregon SUDS, catchment area approx. 1 million), SCA cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…It is made up of nine individual criteria determined from the 12‐lead ECG, with RE score of 4 being labeled as probable LVH and a score of 5 or greater as definite LVH (Romhilt & Estes, ). In addition to diagnosing LVH, the RE score has been shown to predict adverse cardiovascular events and all‐cause mortality (Estes, Zhang, Li, Tereschenko, & Soliman, ; Estes, Zhang, Li, Tereshchenko, & Soliman, ), and we recently demonstrated that one component of the RE score, delayed intrinsicoid deflection, was independently predictive of SCA (Darouian et al., ). However, little data exists on the performance of the other individual components, or the RE score as a whole as a predictor of SCA.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is made up of nine individual criteria determined from the 12‐lead ECG, with RE score of 4 being labeled as probable LVH and a score of 5 or greater as definite LVH (Romhilt & Estes, ). In addition to diagnosing LVH, the RE score has been shown to predict adverse cardiovascular events and all‐cause mortality (Estes, Zhang, Li, Tereschenko, & Soliman, ; Estes, Zhang, Li, Tereshchenko, & Soliman, ), and we recently demonstrated that one component of the RE score, delayed intrinsicoid deflection, was independently predictive of SCA (Darouian et al., ). However, little data exists on the performance of the other individual components, or the RE score as a whole as a predictor of SCA.…”
Section: Introductionmentioning
confidence: 89%
“…We evaluated the relationship of the RE score and SCA from the Oregon Sudden Unexpected Death Study (Oregon SUDS). The details of this ongoing study have been published previously (Chugh et al., ; Darouian et al., ; Narayanan et al., ; Teodorescu et al., ). Cases and controls in the study were enrolled from the Portland, Oregon metropolitan area consisting of a population of approximately one million individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that increased myocardial voltage likely represents adverse “electrical” remodeling, conferring a risk that is distinct from the “anatomic” remodeling of echocardiographic LV hypertrophy . Delayed intrinsicoid deflection (DID) of the QRS complex is an ECG marker that contributes to risk of arrhythmogenesis independent of anatomic increase in LV mass . Delayed QRS transition zone (R‐wave transition at V5 or V6) is another abnormal ECG marker associated with increased SCD risk, likely caused by a pathophysiology that extends beyond previous myocardial infarction and reduced LVEF .…”
mentioning
confidence: 99%
“…10 Delayed intrinsicoid deflection (DID) of the QRS complex is an ECG marker that contributes to risk of arrhythmogenesis independent of anatomic increase in LV mass. 11 Delayed QRS transition zone (Rwave transition at V5 or V6) is another abnormal ECG marker associated with increased SCD risk, likely caused by a pathophysiology that extends beyond previous myocardial infarction and reduced LVEF. 12 Manifestations of abnormal myocardial repolarization have also been linked to increased risk of SCD.…”
mentioning
confidence: 99%